2018
DOI: 10.1210/js.2018-00041
|View full text |Cite
|
Sign up to set email alerts
|

Oral Glucose Tolerance Test Glucose Peak Time Is Most Predictive of Prediabetes and Hepatic Steatosis in Obese Girls

Abstract: Obese adolescent girls are at increased risk for type 2 diabetes, characterized by defects in insulin secretion and action. We sought to determine if later glucose peak timing (>30 minutes), 1-hour glucose >155 mg/dl, or monophasic pattern of glucose excursion during an oral glucose tolerance test (OGTT) reflect a worse cardiometabolic risk profile. Post-pubertal overweight/obese adolescent girls without diabetes were studied (N = 88; age, 15.2 ± 0.2 years; body mass index percentile, 97.7 ± 0.5). All particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 48 publications
3
33
0
Order By: Relevance
“…Our study further found that individuals with multiphasic curves whose plasma glucose concentration reached the lowest point at 60 min had better β-cell function than those with a nadir at 120 min. Consistent with previous studies [26], we found that the earlier the glucose/insulin peak in the OGTT curve, the better the β-cell function.…”
Section: Discussionsupporting
confidence: 92%
“…Our study further found that individuals with multiphasic curves whose plasma glucose concentration reached the lowest point at 60 min had better β-cell function than those with a nadir at 120 min. Consistent with previous studies [26], we found that the earlier the glucose/insulin peak in the OGTT curve, the better the β-cell function.…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, we also identified the monophasic curve shape an unreliable biomarker with the lowest diagnostic sensitivity and specificity at 6-weeks and 1-year compared to all other morphological features. Though previous studies in adolescents with obesity found an association of monophasic curve (compared to the biphasic) with increased insulin resistance (11), more recent data in youth and adults suggest that the monophasic curve has high false positive rates (8, 16). When curve shape is directly compared to the time to glucose peak parameter, the mono/ biphasic curve variable mischaracterized prediabetes status in >50% of cases (8, 16) (37).…”
Section: Discussionmentioning
confidence: 86%
“…Though previous studies in adolescents with obesity found an association of monophasic curve (compared to the biphasic) with increased insulin resistance (11), more recent data in youth and adults suggest that the monophasic curve has high false positive rates (8, 16). When curve shape is directly compared to the time to glucose peak parameter, the mono/ biphasic curve variable mischaracterized prediabetes status in >50% of cases (8, 16) (37). In keeping with these analyses, this study confirms that the monophasic curve shape was associated with lowest reproducibility and modest diagnostic accuracy compared to both glucose peak and 1-hr glucose parameters.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Specifically, risk prediction models for prediabetes were shown to be reliably and independently enhanced by the addition of time-to-peak blood glucose concentration during an oral glucose tolerance test (Chung et al, 2017). Moreover, the use of this statistic in this context theoretically signified the early phase insulin response, which may have provided additional mechanistic insight beyond alternative summary statistics (Cree-Green et al, 2018). A further application of time-to-peak has been to inform methodologies that seek to identify certain responses, such as the duration and sampling frequency of an oral fat tolerance test The time taken to reach the maximum measured value.…”
Section: Time-to-peakmentioning
confidence: 99%